Analysis of natural dyes in archeological textiles using TOF‐SIMS and other analytical techniques. (11th June 2014) - Lee, Jihye; Kim, Man‐Ho; Lee, Kang‐Bong; van Elslande, Elsa; Walter, Philippe; Lee, Yeonhee; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; et al.
<x xml:space="preserve">Abstract</x> Analytical identification of dyes in excavated textiles is an indispensable task for conservation research and restoration of ancient remains. However, excavated textiles have changed in color because of the burial environment and their centuries of burial; also, the color gradually fades after excavation. Furthermore, the low amount and limited availability of samples make it extremely difficult to identify the dyes. Therefore, in this study, non‐destructive analytical instruments such as time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS), Fourier transform infrared spectroscopy (FTIR), and X‐ray photoelectron spectroscopy (XPS) were used for dye detection, and analysis results are compared. In order to compare a dye to another dye, standard samples of dyed silk were prepared using dye compounds such as curcumin, berberine, quercetin, and indigo. These samples were then analyzed with TOF‐SIMS and FTIR. After the methodology to determine the dyes in the textiles was established, surface analytical techniques were also performed on three ancient textiles coming from 18th century Joseon Dynasty tombs. From the TOF‐SIMS and the FTIR spectra, indigo was detected on the blue textile, and indigo and berberine were detected on the green and brown textiles. The results suggest that TOF‐SIMS and FTIR are efficient and complementary non‐destructive techniques for the characterization of excavated fabrics. Copyright © 2014 John Wiley & Sons, Ltd.